French-speaking children’s freely produced labels for facial expressions - Maassarani, Reem; Gosselin, Pierre; Montembeault, Patricia; Gagnon, Mathieu (Frontiers in Psychology, 2014)
In this study, we investigated the labeling of facial expressions in French-speaking children. The participants were 137 French-speaking children, between the ages of 5 and 11 years, recruited from three elementary schools in Ottawa, Ontario, Canada. The facial expressions included expressions of happiness, sadness, fear, surprise, anger, and disgust. Participants were shown one facial expression at a time, and asked to say what the stimulus person was feeling. Participants’ responses were coded by two raters who made judgments concerning the specific emotion category in which the responses belonged. Five- and 6-year-olds were quite accurate in labeling facial expressions of happiness, anger, and sadness but far less accurate for facial expressions of fear, surprise, and disgust. An improvement in accuracy as a function of age was found for fear and surprise only. Labeling facial expressions of disgust proved to be very difficult for the children, even for the 11-year-olds. In order to examine the fit between the model proposed by Widen and Russell (2003) and our data, we looked at the number of participants who had the predicted response patterns. Overall, 88.52% of the participants did. Most of the participants used between 3 and 5 labels, with correspondence percentages varying between 80.00% and 100.00%. Our results suggest that the model proposed by Widen and Russell is not limited to English-speaking children, but also accounts for the sequence of emotion labeling in French-Canadian children.